2022
DOI: 10.1002/rra.4027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of two UAV‐mounted uncooled thermal infrared sensors in predicting river water temperature

Abstract: Measurement by a unmanned aerial vehicles (UAV) equipped with thermal infrared sensors has great potential as a new technique for understanding the spatial heterogeneity of river water temperature; however, the measurement technique has not been established yet. Therefore, this study measured surface and water temperatures using two uncooled thermal infrared sensors, which are commercially available, for 7 months, to obtain knowledge to establish a method for predicting the river water temperature using uncool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Following the method of Niwa (2022), the thermal infrared orthomosaic image created from Altum data was corrected using the measured water temperature. On 2 August 2022, the water temperature was measured at nine sites using CT-300WP (CUSTOM Corporation, Tokyo, Japan) within 1 h after the UAV shooting.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the method of Niwa (2022), the thermal infrared orthomosaic image created from Altum data was corrected using the measured water temperature. On 2 August 2022, the water temperature was measured at nine sites using CT-300WP (CUSTOM Corporation, Tokyo, Japan) within 1 h after the UAV shooting.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Therefore, thermal infrared sensors mounted on UAVs, which can measure surface temperature as an area with high spatial resolution, provide insights into the study of river water temperature. Niwa (2022) used a commercially available thermal infrared sensor mounted on a UAV and showed that river water temperature can be estimated as an area with high spatial resolution. Collas et al (2019) evaluated a suitable habitat for freshwater fish using UAV‐acquired water temperature distributions with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Although TIR cameras can only measure the water temperature at the surface, it is much less labor‐intensive for surveys covering a large spatial scale than direct observation using thermometers or fiber‐optic distributed temperature sensing (FO‐DTS) systems (Hare et al., 2015). For surveys of wide rivers, the spatial distributions of groundwater discharge zones and the stream temperature can be mapped by using a TIR camera mounted on an unmanned aerial vehicle (UAV), helicopter, or aircraft (Dugdale et al., 2022; Niwa, 2022; Rautio et al., 2015; Wilbur et al., 2020). Even for fifth‐order river sites, however, UAV‐based TIR sensing is less suitable for locating groundwater discharge points than handheld TIR imaging owing to their submeter scale and position beneath the riparian tree canopy (Briggs et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…• Real-time thermal imaging helps find suitable sampling points of groundwater discharge differing in chemistry from stream water • Postprocessing of thermal video can easily map springs with thermal anomalies and the spatial distribution of the stream temperature • The water temperature of springs is useful for inferring their sources when multiple groundwater sources contribute to a stream and the stream temperature can be mapped by using a TIR camera mounted on an unmanned aerial vehicle (UAV), helicopter, or aircraft (Dugdale et al, 2022;Niwa, 2022;Rautio et al, 2015;Wilbur et al, 2020). Even for fifth-order river sites, however, UAV-based TIR sensing is less suitable for locating groundwater discharge points than handheld TIR imaging owing to their submeter scale and position beneath the riparian tree canopy (Briggs et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although thermal cameras can only measure the water temperature at the surface, it is much less labor-intensive for surveys with a large spatial scale than direct observation using thermometers or fiber-optic distributed temperature sensing (FO-DTS). For surveys of wide rivers, groundwater discharge zones can be mapped by using a thermal camera mounted on an unmanned aerial vehicle (UAV), helicopter, or aircraft (Dugdale et al, 2022;Niwa, 2022;Rautio et al, 2015;Wilbur et al, 2020). However, this remote sensing technique is difficult to utilize for headwater streams because their channels and riverbanks are often covered by dense riparian trees.…”
Section: Introductionmentioning
confidence: 99%